Short UV-C Treatment Prevents Browning and Extends the Shelf-Life of Fresh-Cut Carambola - Moreno, Carlota (2017)
In this work, we selected a short UV-C treatment for fresh-cut carambola and assessed its efficacy in supplementing the benefits of low temperature storage. UV-C treated (6.0, 10.0, and 12.5 kJm−2) carambola slices showed reduced deterioration compared to control fruit. Treatment with a dose of 12.5 kJm−2 UV-C was more effective in maintaining quality and was selected for subsequent experiments evaluating the combination of UV-C and refrigeration on fruit storability and physical, chemical, and microbiological properties. Short UV-C exposure reduced weight loss and electrolyte leakage. UV-C treated carambola slices presented higher phenolic antioxidants than control after 21 d at 4∘C and showed no alterations in soluble solids or titratable acidity. UV-C exposure also reduced the counts of molds, yeast, and aerobic mesophilic bacteria. UV-C treated fruit showed a fresh-like appearance even after 21 d as opposed to control carambola which presented spoilage and extensive browning symptoms. The reduction of fruit browning in UV-C treated fruit was not due to reduction in phenylalanine-ammonia lyase (PAL) and/or peroxidase (POD), but rather through polyphenol oxidase (PPO) inhibition and improved maintenance of tissue integrity.